Vertical integration and macroeconomic growth: the case of the steel industry - Scheuplein, Christoph (ERDKUNDE, 2010)
As a result of the rise in the raw materials market of 2007–08, steel-producing companies are re-thinking their purchasing of iron ore. Integration of upstream mining companies is one option for ensuring the supply of raw materials. This trend is being pursued mostly in the up-and-coming industrial companies of newly industrializing countries. In contrast, the steel companies of mature industrial countries are continuing to rely on the market. This variation in company strategies cannot be explained by current theories of vertical integration such as the Transaction Cost Approach and the Global Value Chain approach. This only becomes possible by considering the diverse macroeconomic environment, which is characterized by high profit margins and high investment in the newly industrializing countries. Theoretically, this requires us to borrow arguments from François Perroux’s Polarization Theory and arguments from Andreas Predöhl’s Theory of Economic Area Development. This paper contains an empirical investigation of vertical integration based on the steel and iron ore industries, and uses an Indian and a Chinese company as examples.